Potential of interplanted soybean and grain sorghum as a forage for dairy cattle - Shirley, John E.; Evans, J. (Kansas Agricultural Experiment Station, 2012)
Interplanted soybean (l00 to 120 lbs/acre) and grain sorghum (15 to 20 lbs/acre) were harvested at 64,88,102, 123, and 130 days postplanting to determine the ratio and chemical composition of vegetative and seed parts for each plant at advancing stages of maturity. Initial vegetative dry matter yield was 6,300 lbs/acre and increased to 15,000 lbs/acre with 63% vegetative at 123 days postplanting. Vegetative portions (stems, leaves, stalks) of the soybean and grain sorghum plants constituted 100% of the dry matter at day 64, then decreased to 52% at day 130, whereas the contribution of the soy pod (plus bean) and milo head to total dry matter increased from 0% at day 64 to 13% and 35%, respectively, at day 130. Generally, TDN and crude protein decreased over time in the vegetative plant parts and increased in the seed parts, whereas neutral detergent fiber (NDF) increased in the vegetative plant parts and decreased in the seed parts. Chemical composition at day 123 for the vegetative parts was 56% estimated TDN, 46% ADF, and 9% crude protein. NDF was 74% for grain sorghum and 57% for soy, with the difference contributed by hemicellulose. For the grain parts, TDN was 75%; NDF was 40% for grain sorghum and 28% for soy with the difference contributed by hemicellulose; ADF was 18%; and protein was 9% for grain sorghum and 29% for soy.
Keywords: Dairy; Soybean; Grain sorghum; Forage; Protein; Total digestible nutrients (TDN)